Perinatal factors and the risk of atopic dermatitis: A cohort study. Issue 1 (9th December 2013) - Parazzini, Fabio; Cipriani, Sonia; Zinetti, Cornelia; Chatenoud, Liliane; Frigerio, Luigi; Amuso, Giuseppe; Ciammella, Massimo; Di Landro, Anna; Naldi, Luigi
Abstract Objective To analyze the effects of pregnancy and early events in the newborn on the risk of subsequent atopic dermatitis (AD) during the first year of life. Patients and Methods This is a prospective multicenter cohort study of newborns during the first year of life. Newborns identified on random days in three obstetrics departments in the area of Bergamo, Lombardy, Northern Italy, were eligible. At baseline, the mothers were interviewed by medical staff during their stay in hospital after delivery. At 6 and 12 months after delivery, a postal questionnaire was sent to the parents. Relative risks were calculated with and without adjustment by multiple regression analysis. Results A total of 1081 newborns entered the study: 796 (74%) parents answered the 12‐month questionnaire. Hundred and thirty‐eight (17%) reported a diagnosis of AD at 6 months and 222 (28%) at 12 months. Parental history of AD and/or asthma was associated with an increased risk of AD (RR 1.5, 95%CI 1.1–2.0). Birth weight was slightly associated with an increased risk of AD: RR 1.04, 95%CI 1.001–1.08 (continuous variable, increment of 100 grams). No association emerged between breast feeding, smoking, and risk of AD. Conclusions This study in an Italian offspring cohort points to family history of atopic diseases and body weight at birth as relevant risk factors. The study was unable to document associations with other perinatal factors particularly breast feeding and parental smoking in the perinatal period.